Computer 3D Modeling of the Process of Wastewater Treatment in a Settling Tank - Biliaiev, M. M.; Brazaluk, Iu. V.; Kirichenko, P. S.; Mashykhina, P. B.; Kovalenko, A. S. (Nauka ta progres transportu, 2023)
Purpose. Settling tanks are widely used in technological schemes of wastewater treatment. As a rule, horizontal settling tanks are used in practice. However, to increase the efficiency of water treatment in a horizontal settling tank, additional elements can be used, which are placed in different places in the structure. When reconstructing such structures or designing them for new facilities, it is necessary to assess the efficiency of the settling tanks under different operating conditions. To solve this problem, mathematical models play an important role, including conducting physical experiments, which requires considerable time to obtain results. In the case of mathematical modeling of the water treatment process in a sedimentation tank, two problems need to be solved: the hydrodynamic problem and the mass transfer problem. The main purpose of this paper is to develop a 3DCFD model for calculating the impurity concentration field in a sedimentation tank. Methodology. A dynamic multifactorial numerical model was developed for computer calculation of the wastewater treatment process in a settling tank. The hydrodynamics of the wastewater flow in the settling tank was calculated on the basis of a three-dimensional equation for the velocity potential (potential motion model). The calculation of the impurity concentration field in the settling tank was determined by numerical integration of the three-dimensional mass transfer equation. This equation takes into account the non-uniformity of the flow velocity field in the settling tank, the diffusion process, and the gravitational deposition of the impurity in the structure. The numerical integration of the modeled equations was carried out by using finite-difference splitting schemes. Findings. The software implementation of the constructed mathematical model was carried out. The results of a computational experiment to study the process of wastewater treatment in a settling tank with visualization of the calculation results are presented. Originality. A multifactorial three-dimensional CFD model has been developed that allows to quickly assess the efficiency of the settling tank. Practical value. The proposed CFD model can be used in calculations in the design of wastewater treatment systems or to determine the efficiency of wastewater treatment under new operating conditions. Мета. Відстійники широко використовують у технологічних схемах очищення стічних вод. Як правило, на практиці використовують відстійники, що мають горизонтальну форму. Але для підвищення ефективності очищення води в горизонтальному відстійнику можуть бути використані додаткові елементи, які розташовують у споруді в різних місцях. Під час реконструкції таких споруд або проєктування їх для нових підприємств потрібне оцінювання ефективності роботи відстійників за різних умов експлуатації. Для розв’язання цієї задачі важливу роль відіграють математичні моделі, зокрема проведення фізичних експериментів, що потребує значного часу на отримання результатів. У випадку математичного моделювання процесу очищення води у відстійнику потрібно розв’язати дві задачі: гідродинамічну задачу та задачу масопереносу. Основною метою статті є розробка 3DCFD-моделі для розрахунку поля концентрації домішки у відстійнику. Методика. Для комп’ютерного розрахунку процесу очищення стічних вод у відстійнику розраховано динамічну багатофакторну чисельну модель. Гідродинаміку потоку стічних вод у відстійнику розраховано на базі тривимірного рівняння для потенціалу швидкості (модель потенціального руху). Розрахунок поля концентрації домішки у відстійнику визначено шляхом чисельного інтегрування тривимірного рівняння масопереносу. Це рівняння враховує нерівномірність поля швидкості потоку у відстійнику, процес дифузії, гравітаційне осадження домішки у споруді. Чисельне інтегрування модельованих рівнянь здійснено шляхом використання скінченнорізницевих схем розщеплення. Результати. Здійснено програмну реалізацію побудованої математичної моделі. Наведено результати обчислювального експерименту з дослідження процесу очищення стічних вод у відстійнику з візуалізацією результатів розрахунків. Наукова новизна. Розроблено багатофакторну тривимірну CFD-модель, що дозволяє швидко оцінити ефективність роботи відстійника. Практична значимість. Запропонована CFD-модель може бути використана під час проведення розрахунків у випадку проєктування систем очищення стічних вод або для визначення ефективності очищення стічних вод за нових режимів експлуатації.